2018
DOI: 10.1149/2.1251814jes
|View full text |Cite
|
Sign up to set email alerts
|

Ink Solvent Dependence of the Ionomer Distribution in the Catalyst Layer of a PEMFC

Abstract: This study examines the effect of ink composition on the ionomer distribution in the catalyst layer of membrane electrode assemblies (MEA) prepared by decal transfer. We combine both structural and electrochemical characterization techniques to investigate the influence of the ionomer distribution on MEA performance determined by 50 cm 2 active area single-cell proton exchange membrane (PEM) fuel cell measurements. Cathodic catalyst layers were prepared from inks with different alcohols (1-propanol or 2-propan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
88
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(90 citation statements)
references
References 47 publications
1
88
1
Order By: Relevance
“…Membrane electrode assembly preparation.-All membrane electrode assemblies (MEAs) used in this study were prepared by the decal transfer method. 36 All electrodes used were manufactured in-house according to Orfanidi et al 37 Catalyst inks were prepared by mixing first the catalyst powder with water, followed by solvent 1-propanol and last the ionomer dispersion containing water-solvent (725 EW 3 M dry powder dispersed in 40% H 2 O / 60% 1-propanol, resulting in a 18 wt% ionomer solution) in a 15 ml HDPE capped bottle containing 26.5 g of 5 mm ZrO 2 beads. In order to obtain an appropriate viscosity for the coating process, the solids content of the ink was set to 0.03 g ml ink −1 and the water content was adjusted to 16 wt%.…”
Section: Methodsmentioning
confidence: 99%
“…Membrane electrode assembly preparation.-All membrane electrode assemblies (MEAs) used in this study were prepared by the decal transfer method. 36 All electrodes used were manufactured in-house according to Orfanidi et al 37 Catalyst inks were prepared by mixing first the catalyst powder with water, followed by solvent 1-propanol and last the ionomer dispersion containing water-solvent (725 EW 3 M dry powder dispersed in 40% H 2 O / 60% 1-propanol, resulting in a 18 wt% ionomer solution) in a 15 ml HDPE capped bottle containing 26.5 g of 5 mm ZrO 2 beads. In order to obtain an appropriate viscosity for the coating process, the solids content of the ink was set to 0.03 g ml ink −1 and the water content was adjusted to 16 wt%.…”
Section: Methodsmentioning
confidence: 99%
“…Optimization of porous electrodes has been achieved by controlling relative amounts of the ionomer and/or electrocatalyst if the polymer electrolyte membranes are fixed [7][8][9][10]. It has been reported that the distribution of ionomer within the carbon supported electrocatalyst (e.g., Pt/C) plays an important role in the design of high-performance porous electrode catalyst layers (CLs), as the transport of species such as oxygen and protons is controlled by the thickness of the ionomer on the catalyst surface and the continuity of the ionomer and gas networks in the CL, with the transport of electrons being related to the continuity of the carbon particle network [11][12][13][14][15][16]. The structural change of CLs significantly influences Pt utilization by the attachment of ionomers onto the carbon support of the Pt electrocatalyst [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was recently demonstrated that, in carbon-supported catalysts, not only oxygen diffusion can be rate limiting, but also proton transport 15 . Using new catalyst layer engineering methods, oxygen-related mass transport resistances can be to some extent overcome 16,17 . A disruptive change of the catalyst layer concept towards self-supported catalyst layers would allow new operation regimes for PEMFCs with regard to temperature and humidification.…”
mentioning
confidence: 99%